A HERMENEUTICAL APPROACH TO “IN SOLEMNITATE CORPORIS CHRISTI” BY EDUARD TERÉNYI - Anamaria Mădălina HOTORAN (Studia Universitatis Babeş-Bolyai. Musica)
In the organ play In solemnitate corporis Christi (1993), the variational principles aims to a macro and micro-structure as well. The first part represents the pattern for the next two parts, it becomes a sort of “theme – personage” in the mind of the author through the preservation of the algorithm of the three segments A, b, c that are characterized through different syntaxes: A - melody, b - chords/figurations, c – unison/eighths/chords. The first strophe A is a melodic line of a neo – Gregorian style that is partially inspired from the cantus planus variant of In solemnitate corporis Christi from Cantionale Catholicum. The b and c segments are, in fact, stylemes that can be found in other Terényian musical works as well, as they metaphorically reflect God’s voice or “the divine reality”. The stylistic benchmark of the b segment is represented by the third part of the musical play L’Ascension by O. Messiaen, which, through the title and its motto corresponds to the spiritual ideas of In solemnitate corporis Christi. The c segment is the second styleme as parallel octaves in long rhythmic values and it has the connotation of the divine voice. This leitmotif in itself presents in the Terényian creation some variants, as a sacra emblem. It can be a row of three – four parallel chords or octaves in extreme nuances (ppp or fff), or alternating abrupt contrasts of the dynamics (fff ® pp ® fff and so on). We can meet it in the organ plays of the author, in contexts that have the same theophany meaning: a revelation of the divine in the person of Christ (In solemnitate corporis Christi, Epiphania Domini), the celebration of God in a cosmic liturgical frame (Glocken) or in the middle of the monumental cathedral of the nature (Stella aurorae, The Birds), the divine light and word (Semper felice, Introitus), Christ’s sadness (In solemnitate corporis Christi), God’s wrath (Die Gottestrompeten), or even Holy Mary’s image (Stella aurorae, Glocken). In solemnitate corporis Christi depicts “a sonorous fresco of the last Supper that precedes the suffering and the death of Christ. It is a commemoration of the scene in which the Saviour talks about himself and the mission He has to fulfil onto the earth” (E. Terényi). Taking as a basis the interview with the composer (February 2008), we will follow the transformation of the three paradigmatic models A, b, c, as linked to the succession of the ideas/images that the author himself has set, without affecting the autonomy of the sonorous image.